Fluorescence resonance energy transfer-based ratiometric fluorescent assay for highly sensitive and selective determination of sulfide anions1. Issue 19 (7th October 2015) - Liang, Meijuan; Chen, Yonglei; Zhang, Haijuan; Niu, Xiaoying; Xu, Laifang; Ren, Cuiling; Chen, Xingguo
<x xml:space="preserve">Abstract</x> A novel and effective ratiometric fluorescence strategy was developed for rapidly, sensitively and selectively probing sulfide anions (S2−).